関節突起を含む下顎枝に多発した骨形成線維腫の1例 - 濱田, 良樹; 福岡, 愛理; 重松, 宏昭; 小川, 匠; 中谷, 逸希; 中岡, 一敏 (日本口腔外科学会雑誌, 2018)
We report a case of multiple ossifying fibromas arising in the mandibular ramus, including the condylar process. A 19-year-old woman was referred to our clinic by her dentist because radiolucent lesions were detected in the right side of the mandible on a panoramic radiograph. Although she had no symptoms, CT images revealed multiple lesions in the right mandibular angle (lower lesion) and condylar process (upper lesion). At first, complete removal of the lower lesion and partial removal of the upper lesion were performed with the use of a surgical template for pathological diagnosis. The specimens were definitely diagnosed as ossifying fibroma. Secondarily, we completely resected the upper lesion by open temporomandibular joint surgery. The bone defect of the condyle after tumor removal was immediately reconstructed with particulate cancellous bone and marrow harvested from the iliac crest. There was no evidence of recurrence or jaw dysfunction at the 3-year follow-up after surgery.